Studies on the Biology and Effect of Seasonal Variation on the Growth and Silk Production by Erisilk Worm Philosamia Bioini Hutt. - Sachan, J N; Bajpai, S P (Annals of Arid Zone, 2016)
The studies on the biology of Erisilk worm Philosamiaricini were undertaken, keeping in view to explore thepossibility of its successful rearing in different months ofthe year in the semi-arid regions of Rajasthan wherecastor is grown abundantly with a little irrigation. Studieswere conducted on local castor variety and was foundthat total life cycle of Erisilk worm is about 46, 59 and88 days in first second and third generation respectively.During August-September the mean temperature 27.34°C±5°C and humidity 78% ± )0 were found most favourablefor larval growth, weight of cocoon and in shorteningthe duration of life cycle. Where as the period Februaryto April when mean temperature 1430e ± SOC and humidity38.7% ± 10 were found unfavourable. Present studieshave proved that farmers can take the rearing of castorsilk worm in the region successfully, except in the summermonths.